Can emotional states interfere with self-esteem and mental health during pandemic context on health students in low middle-income country? (Research, Society and Development, 2022)
The university experience is considered a factor that increases stress and affects health of students. Studies have shown distancing measure is associated with depression in young adults. This study aimed to assess the impacts of social isolation on health students due the COVID-19 pandemic. It is a primary study sought to investigate the levels of depression, anxiety and stress by DASS-21, mental components by SF-36, and self-esteem by RSES. The 358 health students accessed the form. The average age was 23.4 years, 75.4% women, and 24.6% men. We divided the selected groups for comparative analysis between academic degree (Undergraduate student-UG/Graduate student-G), gender (Women-W/Men-M) and practitioners of physical activity (Yes-Y/No-N). Principal Component Analysis showed the DASS-21, RSES and SF-36 scales interact into two dimensions that correlate positively and negatively. The findings showed UG suffer greater pressure on mental states than G (W